Platform Power and Policy in Transforming Television Markets - Evens, Tom. author. aut Link
IX, 304 p. 7 illus.
Keywords: This book seeks to investigate ‘platform power’ in the multi-platform era and unravels the evolution of power structures in the TV industry as a result of platformisation. Multiple TV platforms and modes of distribution are competing–not necessarily in a zero-sum game–to control the market. In the volume, the contributors work to extend established ‘platform theory’ to the TV industry, which has become increasingly organised as a platform economy. The book helps to understand how platform power arises in the industry, how it destabilises international relations, and how it is used in the global media value chain. Platform Power and Policy in Transforming Television Markets contributes to the growing field of media industry studies, and draws on scholarly work in communication, political economy and public policy whilst providing a deeper insight into the transformation of the TV industry from an economic, political and consumer level. Avoiding a merely legal analysis from a technology-driven perspective, the book provides a critical analysis of the dominant modes of power within the evolving structures of the global TV value chain. .